Valuing mobility in a post COVID-19 world. Issue 1 (2nd January 2021) - Cresswell, Tim
ABSTRACT: How do we, might we, value mobility post COVID-19? This is the central question addressed in this paper. The mobilities turn, or 'new mobilities paradigm' had many starting points, but one of them was a general revaluing of mobility. Examples ranged from the opening up of the supposed 'dead time' of the journey to work to the general critique of a sedentarist metaphysics across social, cultural and political thought. With this in mind, the onset of COVID-19 along with the closing down of national borders, virtual elimination of air passenger travel, and variety of lockdowns and quarantine policies at more local scales, raises several questions about the valuing of mobility in the 21st Century. While conservative and nationalist commentators seek to hunker down in various forms of national localism more critical commentators are identifying the landscape of connected capitalism as a root cause of the current crisis. The paper explores the changed landscape of local, national and global mobilities in order to ask how we might continue to value mobilities into the future.